PENGARUH CITRA PERUSAHAAN DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN (Studi Kasus Pasien Rumah Sakit Annisa Pekanbaru) - Emilia, Sepni; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This assessment was carried out at the Pekanbaru Annisa Hospital, located at Jalan Garuda No.66, Pekanbaru. The purpose of this study is to find out how much influence the Company Image and Service Quality on Patient Satisfaction at Pekanbaru Annisa Hospital. The sample in this study was taken as many as 100 respondents and the technique used was accidental sampling. The data in this study used the survey method through questionnaires filled out by patients. Data obtained from the questionnaire and then processed to then be tested through statistics using the SPSS program. From the results of testing conducted shows that the Corporate Image and Service Quality have a positive and significant effect on Patient Satisfaction at Pekanbaru Annisa Hospital. With an R2 value of 0.787. This shows that the Corporate Image and Service Quality have an effect of 78,7% on Patient Satisfaction at Annisa Pekanbaru Hospital, while the remaining 21,3% is influenced by other variables not examined in this study.Keywords: Company Image, Service Quality and Patient Satisfaction